Sustainable Active Packaging: Essential Oil-Enhanced Rice Starch Film for Preserving Fried Foods - Teerin Chysirichote; Thitirat Khanthong; Nonthiya Khampanin (Applied Food Research, 2025)
• Acetylation improved strength and water resistance of rice starch film. • Film flexibility increased after rice starch acetylation. • Lemongrass oil enhanced antioxidant and antimicrobial activity. • Active film extended pork crackling shelf life by 52% at 30°C. • Developed film shows strong potential for food packaging application. This study develops a biodegradable, edible packaging film made from acetylated rice starch and enhanced with essential oils (EOs) to improve food preservation. Three EOs, including ginger, holy basil, and lemongrass, were selected for their well-documented antimicrobial and antioxidant activities as well as their relevance to regional culinary applications. The combination of EO-based antimicrobial properties with modified starch extended the shelf life of a typical fried food. The effects of acetylation at degrees of substitution (DS) of 1.0, 1.8, and 3.0 on the film’s physical, mechanical, and barrier properties were investigated. The film with DS 1.8 exhibited optimal properties, including low water solubility (15.3 %), low water vapor permeability (10 × 10⁻¹¹ g·m⁻¹·s⁻¹·Pa⁻¹), and high flexibility and tensile strength. The optimized acetylated rice starch film (ARSF) with the selected EOs was then evaluated for antimicrobial and antioxidant activities. Among the tested oils, lemongrass EO showed the strongest antibacterial and antifungal activities, supporting its emphasis as the most promising candidate for improving product shelf life. Predictive modeling demonstrated that the application of the optimized EO-enhanced ARSF (EO-ARSF) significantly prolonged the shelf life of pork crackling stored at 30°C, increasing it from 37.8 days with ARSF alone to 57.7 days with EO-ARSF. These results emphasize the attractiveness of EO-ARSF, particularly lemongrass-enriched films, as a sustainable, industrially applicable packaging material for fried foods, combining functional preservation properties with eco-friendly design.
Keywords: Nanocomposite Films for Food Packaging; Food composition and properties; biodegradable polymer synthesis and properties